Glutathione S-transferase gene polymorphism: Relation to cardiac iron overload in Egyptian patients with Beta Thalassemia Major. Issue 1 (2nd January 2016) - Mokhtar, Galila M.; Sherif, Eman M.; Habeeb, Nevin M.; Abdelmaksoud, Abeer A.; El-Ghoroury, Eman A.; Ibrahim, Ahmed S.; Hamed, Enas M.
Abstract : Objectives : Estimating the prevalence of glutathione S -transferase gene polymorphism (GSTM1) null genotype among patients with beta thalassemia major (β-TM) in relation to myocardial status assessed by tissue Doppler and cardiac siderosis assessed by cardiac magnetic resonance imaging (MRI) T2*. Methods : Hundred patients with β-TM and 100 healthy controls were enrolled. Complete blood count (CBC), mean serum ferritin and GSTM1 genotyping, echocardiography, tissue Doppler, and cardiac MRI T2* were done. Results : Serum ferritin ranged from 1200 to 8000 ng/ml, and mean T2* value was 27.10 ± 11.20 ms. Of patients, 68 (68%) had no cardiac siderosis, while 24 (24%) with mild to moderate, and 8 (8%) with sever cardiac siderosis. T2* values were not correlated with serum ferritin ( r = −0.09, P = 0.50). GSTM1 null genotype was prevalent in 46% of patients and 40% of controls ( P = 0.69). Patients with null genotype had significantly shorter T2* ( P = 0.001), higher left ventricular end-diastolic diameter ( P = 0.002), and shorter ejection time ( P = 0.005) with no significant relation to serum ferritin ( P = 0.122). GSTM1 null genotype was the only predictor for cardiac iron overload ( P = 0.002). Discussion : Serum ferritin concentrations have been shown to correlate poorly with all stages of cardiac dysfunction. Low cardiac MRI T2* values occur in patients with β-TM despite good chelation therapy, suggesting a possible role of genetic factors in cardiac siderosis. Conclusion : GSTM1 null genotype is significantly associated with cardiac iron overload independent of serum ferritin in Egyptian patients with β-TM.